SOCIO-PSYCHOLOGICAL CHARACTERISTICS OF INTERPERSONAL RELATIONSHIPS IN THE STUDENT COMMUNITY - Shohsanam Yulchiyeva; Mirkarim Raimdjanov (European Science Publishing, 2024)
The article presents the psychological characteristics of communication and interpersonal relations of students from the Mordovian diaspora. Based on the results of the empirical study, conclusions were drawn about the need to optimize communication and interpersonal relations of students of different nationalities in a university setting through specialized trainings.
Keywords: communication, interpersonal relations, Mordovian diaspora, students, strategies of behavior in conflict, communication skills, empathic abilities.